On Functions of Verbal Nouns in Old and Middle Czech - Pergler, Jiří (Bohemica Olomucensia, 2017)
The paper deals with the functions of verbal nouns in Old and Middle Czech, analyzing the onomasiological categories that are employed with these nouns. As in contemporary Czech, action nouns represent by far the most frequent (paradigmatic) category; however, there are some differences between them and their contemporary-Czech counterparts, among which different valence possibilities stand out. Other frequently represented categories are nouns of results, means, qualities and places, the rest of the categories (such as agent nouns) being rather marginal. The article shows that this arrangement of categories (including their paradigmaticity) is not accidental but corresponds to the general relations between these categories, which are reflected in the distribution of a number of other derivative formants. These relations have been previously described by a semantic map; this paper shows that the semantic map methodology might be a useful tool also for the analysis of the degree of paradigmaticity of onomasiological categories in word formation.
Keywords: verbal noun; word formation; Old Czech; Middle Czech; action noun